"Tungo sa kaligtasan" fire disaster management guidelines for the 400 year old San Agustin Church in Intramuros, Manila balancing optimum protection and minimal intervention - Belgica, Marvin M.; Bulaong, Carmen Bettina S. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The rapid growth in the development of organized groups concentrating their efforts in the conservation of structures deemed of historical significance suggests the evolution on the people's perception towards the importance and meaning of such. Behind this study is the notion that heritage is an integral part of the society because it shapes society where it is situated. In turn heritage is shaped by the needs and dynamics of that society. This relationship suggests that people need to steward for these structures as it resonates us as a society, hence, it is important that we protect these heritage. Now that we are faced by the challenges of climate change, heritage structures has become more vulnerable when it comes to the threats of natural calamities. Although in the recent years, efforts to identify and improve our understanding on how to address the issues faced by heritage structures in light of climate change has been extensive, it is still difficult to pin point a general measure that will solve this problem, as in the words of Thomas Will and Hans Rudolf-Meier 'in heritage conservation disaster mitigation is a question of choice and optimization'. Likewise, it is remarkable that in the course of time that research has dwell on this topic, those pertaining to fire disaster is limited. Therefore, the author thinks that it is also of high value to exhaust the same amount of energy on fire disaster as it is seen as equally destructive, hence the Filipino maxim 'mabuti ng manakawan kaysa masunugan'. In the Philippines, heritage conservation is said to be at its infancy stage, meaning there is more room for improvement, hence, this study's conduct of developing a Fire Disaster Management Plan for one of the country's heritage icons is a step closer to further the discipline.
includes appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Fire prevention -- San Agustin Church (Manila); Risk management -- San Agustin Church (Manila)